REPRESENTASI IDENTITAS AGAMA DALAM KONSEP SPIRITUALITAS MELALUI KONFLIK CERITA FILM JOKOWI - Pamungkas, Albertus Angga Adi; Sjafi'i, Achmad (Seni Media Rekam ISI Surakarta, 2012)
The way in conveying the teachings of every religion known as religious identity. Filmshould be able to make sense of religious identity in the concept of spirituality as a universal wayto convey his message.Research on the representation of religious identity in the Jokowi aims tolook religious values which presenting in one of the central elements of narrative, the conflict.Representation of the concept of spirituality contained in the teachings of education in thefamily, attitudes courage, honesty, social norms, tolerance, and devotion to parents who allcomes down to the rules of how a man should live.All of this,is a form of representation of thereligious teachings of Islam on these aspects.This analysis uses the Cultural Circuit model to seethe representation system that worked on the Jokowi.Keywords:Religion,representation,identity,spirituality,and conflict.